Mate Taon seasonal calendar, ethnographic communication study of Semende Darat community - Yenrizal Yenrizal; Ahmad Muhaimin (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
The Mate Taon calendar is a seasonal calendar typically used by the Semende Darat community, Muara Enim Regency, South Sumatra. This calendar serves as a reference for the agricultural activities of the community established by their ancestors. The aim of this research is to understand the characteristics of mate taon as well as the current knowledge and understanding of the community. This qualitative research employed the ethnographic communication approach. The findings indicate that mate taon represents the community's interpretation of the local natural environment since the time of the puyang and has persisted to the present day. Currently, there are variations in the understanding of the mate taoncalendar, categorized among older generations, adults, and youth. The older generation tends to have a better understanding of mate taon, while adults also comprehend it, albeit not in a substantial manner. In contrast, the youth's understanding is largely superficial. Overall, mate taon continues to be practiced, although it is not substantially understood by the younger generation.